ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI RUMPUT LAUT DENGAN METODE LONG-LINE DI DESA GANSAL - Seakanan, Maria Aldegonda; A Zaenuddin, Ruslan; Puspapratiwi, Dian (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Gansal Village is one of the villages located in the Banggai Islands, which has a significant production of seaweed, especially in the Tinangkung Selatan District. The seaweed production obtained in Gansal Village is relatively high; however, this does not necessarily mean that the income earned is also high. Therefore, a study is needed to analyze the income and feasibility of seaweed farming in Gansal Village, with the determination of respondents conducted using simple random sampling method. A total of 26 respondents were sampled from a population of 113 farmers (23%) who cultivate seaweed. The analysis results indicate that the average income per farmer from one production cycle in Gansal Village, Tinangkung Selatan District, Banggai Islands Regency is Rp. 13,351,903. The analysis shows that the R/C Ratio for seaweed farming is 4.3, indicating that seaweed farming in Gansal Village, Tinangkung Selatan District, is feasible. To further optimize this potential, it is important for the government and related institutions to provide training and extension services to farmers on more efficient and environmentally friendly cultivation techniques. It is also hoped that seaweed farming in Gansal Village will not only develop better but also provide a broader positive impact on the community and the regional economy.